Lipoprotein (a) and risk of cardiovascular disease: a systematic review and meta analysis of prospective studies - Genser, Bernd; Dias, Karen C.; Siekmeier, Ruediger; Stojakovic, Tatjana; Grammer, Tanja B.; März, Winfried (Clinical laboratory, 2011)
Background: Several studies have investigated the role of Lipoprotein (a) as a risk factor for cardiovascular disease (CVD) and have produced controversial results. Data Sources: We conducted a systematic literature review in the databases MEDLINE, EMBASE, and COCHRANE aimed at retrieving prospective studies that investigated the prognostic value of Lipoprotein (a) concentrations on cardiovascular risk and mortality. Methods: From each study we extracted estimates of risk ratios (RR) with respect to the risk of CVD (endpoints: all coronary heart disease (CHD) events pooled, major coronary events, myocardial infarction, stroke) and all cause mortality. Study specific risk ratios were standardised to contrast the top third with the bottom third of the study specific Lipoprotein (a) distribution. Pooled summary estimates were calculated by using fixed and random effects meta analysis techniques, in total and stratified by study design and study population. Results: For the present meta analysis we selected 67 prospective studies including 181,683 individuals. Synthesising data from 37 studies that reported estimates for the endpoint ‘CHD events’ resulted in a RR of 1.57 (95 % CI: 1.41 to 1.75, p < 0.001). For this endpoint subgroup analyses by design and population showed significant estimates: population based cohort studies: n = 15 studies, RR = 1.48 (95 %CI: 1.26 to 1.74, p < 0.001), cohort studies including patients with previous disease: total: n = 11 studies, RR = 1.67 (95 % CI: 1.28 to 2.17, p < 0.001), with CHD: n = 6 studies, RR = 2.37 (95 % CI: 1.41 to 3.97, p = 0.001), nested case control studies: n = 11 studies, RR = 1.64 (95 % CI: 1.47 to 1.83, p < 0.001). We did not find any significant effect on risk of stroke (n = 16 studies, RR = 1.10 (95 % CI: 0.97 to 1.25, p = 0.137)) and mortality (n = 9 studies, RR = 1.12 (95 % CI: 0.94 to 1.33, p = 0.200)). Conclusions: This meta analysis of prospective studies shows a clear association between elevated Lipoprotein (a) levels and increased risk of CHD. This effect is substantially higher in individuals with previous CHD. Our systematic review showed no evidence of an effect on stroke and all cause mortality.